(untitled) (Italian Journal of Public Health, 2011)
Background: Pakistan’s population is estimated to be 160,943,000. It ranks third among the ten high burden countries and accounts for up to 7% of worldwide neonatal deaths. According to the Pakistan’s World Health Organization (WHO 2010) health profile, only 28% of Pakistani women have used ante natal care services (4 plus visits), whilst 39% of reported births in Pakistan had used skilled birth attendant services, whereas 59% fell within the WHO’s regional average. There is also a significant disparity, reported by the WHO, in terms of inequity between the poor and the rich in the use of skilled birth attendant services: 16% and 77 % respectively. Objective: This ethnographic study explores the perceptions about the need for antenatal care (ANC) in a disadvantaged population in Pakistan. Method: This is an Ethnographic study which makes use of standard methods such as non-participant observation, semi structured interviews, and documentary review. Data was collected over 14 months and was analyzed thematically. Key informants assisted in understanding the community norms. Open ended answer options were used in the questionnaire. Setting: The community in this case was an urban squatter settlement by the name of Ghazi Goth, which is the neighborhood of the poor people. Results: We found that 41% of the women did not receive ANC because of lack of financial support. 33% said that family did not support the decision. In 43% of the cases, the husband was the decision maker regarding where the delivery of the baby should take place. 31% of the respondents also reported that their mother-in- laws were the decision makers for the baby’s delivery. Only 3% reported a self decision. Conclusions: This a qualitative study which helps explore perceptions and attitudes of women towards ANC, through contextual data. The study shows that denied access to ANC services is a result of lack of resources, limited mobility and cultural factors.